2020
DOI: 10.1016/j.foodqual.2020.103928
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationships between taste phenotypes, genotypes, ethnicity, gender and taste perception using Chi-square and regression tree analysis

Abstract: It is well known that perceived taste intensity varies greatly among individuals, and that several factors including taste phenotypes (PROP Taster Status (PTS), Sweet Liking Status (SLS), Thermal Taster Status (TTS)), ethnicity and gender, contribute to variation in taste responsiveness, although such factors are usually investigated in isolation. This study aimed to investigate the association between different taste pheno/genotypes, explore whether these taste phenotypes associated with ethnicity (Caucasian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 91 publications
5
20
0
Order By: Relevance
“…The same is evident for Japanese and Chinese respondents. This being said, there have been suggestions that taste sensitivity differs between ethnicity, and Yang et al [ 53 ] found an Asian population to have higher overall taste sensitivity than a Caucasian one.…”
Section: Discussionmentioning
confidence: 99%
“…The same is evident for Japanese and Chinese respondents. This being said, there have been suggestions that taste sensitivity differs between ethnicity, and Yang et al [ 53 ] found an Asian population to have higher overall taste sensitivity than a Caucasian one.…”
Section: Discussionmentioning
confidence: 99%
“…2009), indicate that cultural/national background of a panelist may influence taste perception, since common polymorphisms in genes that are engaged in taste perception are in charge of interindividual differences associated with food preferences within and inbetween populations. Also, Yang et al (2020) confirmed that ethnicity may be one of influential factors in perceiving intensity of five basic tastes. When it comes to different cross-cultural panels engaged, this factor can be pronounced if higher level of variability between panels exists (Teo et al, 2018).…”
Section: Demographic Structure Of Sensory Panelsmentioning
confidence: 65%
“…When it comes to gender, a number of females in trained sensory panels were slightly prevailing although most of the sensory panels did not follow any "gender balance" procedure. There are conflicting studies associated with gender perception of tastes from the ones confirming differences (Hirokawa, Yamazawa, & Shimizu, 2006) to the ones failing to raise such a conclusion (Yang, Williamson, Hasted, & Hort, 2020). Giovannelli et al (2016) assume gender differences in the processing of time associated with olfactory stimulation while Proserpio, Laureati, Invitti, Cattaneo, and Pagliarini (2017) associate body mass index and gender as combining factors influencing differences.…”
Section: Demographic Structure Of Sensory Panelsmentioning
confidence: 99%
“…Measures of overall differences in orosensory responsiveness, such as taste phenotypes [22][23][24], can be used as general proxies for responsiveness (e.g., [25][26][27]). The most well-established taste phenotype from literature is PROP taster status (PTS).…”
Section: Prop Taster Statusmentioning
confidence: 99%